Prevalence of insulin resistance in Chinese solar greenhouse and field workers: evidence from a solar greenhouse and field workers study - Yan, Tenglong; Wang, Minghui; Yang, Siwen; Wang, Yuqian; Zhou, Xingfan; Zhu, Xiaojun; Ma, Wenjun; Tang, Shichuan; Li, Jue (Frontiers in Public Health, 2023)
Evidences suggests that agricultural workers have a higher risk of insulin resistance (IR), but few studies have investigated IR in solar greenhouse workers, who are exposed to higher concentrations of agricultural risk factors compared tothan the traditional agricultural workers. A prevalence study was conducted in a greenhouse vegetable base in China. 948 participants were included in this study., 721 participants were divided into the greenhouse worker group (G group) and 227 participants were divided into the field worker group (F group). The TyG index, which is an indicator to evaluate prediabetes (IR), was calculated by the formula: TyG index = ln [fasting triglycerides (mg/dL) × fasting plasma glucose (mg/dL)/2]. To evaluate the associations of TyG index alternation with solar greenhouse and field work, the multiple linear regression (MLR) and the logistic regression models were performed. The TyG index in the G group (8.53 ± 0.56) was higher than that in the F group (8.44 ± 0.59) (p < 0.05). Solar greenhouse work was positively associated with increased of TyG index in both the multiple linear regression model [β = 0.207, (0.006, 0.408)] and in logistic regression model [OR = 1.469, (1.070, 2.016)]. IR wais associated with the solar greenhouse work. However, the determination of agricultural hazard factors needs to be further strengthened to improve exposure assessment.